Enhanced Hydrogen Generation through Low-Temperature Plasma Treatment of Waste Aluminum for Hydrolysis Reaction - Urbonavicius, Marius; Varnagiris, Sarunas; Knoks, Ainars; Mezulis, Ansis; Kleperis, Janis; Richter, Christiaan; Meirbekova, Rauan; Gunnarsson, Gudmundur; Milcius, Darius (MDPI, 2024)
This study investigates the low-temperature hydrogen plasma treatment approach for the improvement of hydrogen generation through waste aluminum (Al) reactions with water and electricity generation via proton-exchange membrane fuel cell (PEM FC). Waste Al scraps were subjected to ball milling and treated using two different low-temperature plasma regimes: Diode and magnetron-initiated plasma treatment. Hydrolysis experiments were conducted using powders with different treatments, varying molarities, and reaction temperatures to assess hydrogen generation, reaction kinetics, and activation energy. The results indicate that magnetron-initiated plasma treatment significantly enhances the hydrolysis reaction kinetics compared to untreated powders or those treated with diode-generated plasma. Analysis of chemical bonds revealed that magnetron-initiated hydrogen plasma treatment takes advantage by promoting a dual procedure: Surface cleaning and Al nanocluster deposition on top of Al powders. Moreover, it was modeled that such H2 plasma could penetrate up to 150 Å depth. Meanwhile, electricity generation tests demonstrate that only 0.2 g of treated Al powder can generate approximately 1 V for over 300 s under a constant 2.5 Ω load and 1.5 V for 2700 s with a spinning fan. © 2024 by the authors. --//-- This is an open-access article Urbonavicius, M.; Varnagiris, S.; Knoks, A.; Mezulis, A.; Kleperis, J.; Richter, C.; Meirbekova, R.; Gunnarsson, G.; Milcius, D. Enhanced Hydrogen Generation through Low-Temperature Plasma Treatment of Waste Aluminum for Hydrolysis Reaction. Materials 2024, 17, 2637. https://doi.org/10.3390/ma17112637 published under the CC BY 4.0 licence.
This research was funded by the Baltic Research Programme project No. EEA-RESEARCH-92 (Aluminium in circle economy-from waste through hydrogen energy to alumina - AliCE-Why), EEA Grant of Iceland, Liechtenstein and Norway No. EEZ/BPP/VIAA/2021/5. The Institute of Solid State Physics, University of Latvia, as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; electricity generation; hydrogen generation; hydrolysis; PEM fuel cell; plasma treatment; recycling; waste aluminum; waste reduction